Responsiveness in the digital governance system for complaint services at the East Java Provincial Education Office - Luthfiyyah Nabiilah; Vidya Imanuari Pertiwi (Universitas Muhammadiyah Malang, 2025)
This study examines the responsiveness of the digital governance system for complaint services at the East Java Provincial Education Office through the SP4N LAPOR application. The research problem begins with the still-high number of public complaints about education services, despite the availability of a digital complaint system. This study aims to describe how responsive the complaint service is, including the obstacles that arise. This research method uses a qualitative case study approach; data is obtained through in-depth interviews, observation, and documentation, which are analyzed using the interactive model of Miles et al. (data collection, condensation, presentation, and concluding). The results of the study indicate that the six indicators of responsiveness according to Zeithaml — community responsiveness, speed, accuracy, precision, timeliness, and the ability to respond to complaints — have been implemented quite well. However, there are still obstacles, such as delays in re-verifying complaints. In conclusion, the implementation of SP4N LAPOR at the East Java Provincial Education Office is an important innovation in public education services, but still requires improvement in coordination and monitoring to be more optimal. Penelitian ini mengkaji responsivitas dalam sistem tata kelola digital pelayanan pengaduan di Dinas Pendidikan Provinsi Jawa Timur melalui aplikasi SP4N LAPOR. Masalah penelitian berangkat dari tingginya jumlah pengaduan masyarakat terkait layanan pendidikan, meskipun sudah tersedia sistem pengaduan digital. Penelitian ini bertujuan mendeskripsikan bagaimana responsivitas pelayanan pengaduan dijalankan, termasuk hambatan yang muncul. Metode penelitian ini menggunakan pendekatan kualitatif studi kasus, data diperoleh melalui wawancara mendalam, observasi, dan dokumentasi, yang dianalisis dengan model interaktif Miles et al. (pengumpulan data, kondensasi, penyajian, penarikan kesimpulan). Hasil penelitian menunjukkan bahwa keenam indikator responsivitas menurut Zeithaml, yakni kemampuan merespons masyarakat, kecepatan, ketepatan, kecermatan, ketepatan waktu, serta kemampuan merespons keluhan, telah diterapkan cukup baik meski masih terdapat kendala seperti keterlambatan verifikasi ulang aduan. Kesimpulannya, penerapan SP4N LAPOR di Dinas Pendidikan Provinsi Jawa Timur menjadi inovasi penting dalam pelayanan publik pendidikan, namun tetap memerlukan perbaikan pada aspek koordinasi dan monitoring agar lebih optimal. Penelitian ini hanya terbatas pada Provinsi Jawa Timur, sehingga studi lanjutan dapat dilakukan pada wilayah lain untuk memberikan perbandingan yang lebih luas.